Advances at AIDS 2014. What does the future look like and how can we better use the tools we have now?. (December 2014) - Wright, Cameron
Abstract: During July 2014, the International AIDS Conference, AIDS 2014, was held in Melbourne, Australia. Approximately 13 600 delegates took part, and this brief report from an Australian pharmacist who attended outlines some of the drug‐related developments discussed during the 6‐day meeting. There is also an AIDS 2014 YouTube channel through which many sessions from the conference can be accessed without charge.